Diagnosis and Treatment of Aniseikonia from Ocular Asymmetry. - Kundart, James; Citek, Karl; Yudcovitch, Lorne; Hayes, John R.; Ramaswamy, Shankaran (Optometry & Visual Performance, 2025)
Purpose: Aniseikonia, a perceived difference in retinal image sizes, can be caused by structural asymmetry between the eyes, even in the absence of anisometropia or differences in axial length. While refractive and axial aniseikonia can be quantified by measuring structural differences between the two eyes, there is little research on the quantitative effect of retinal asymmetry on the size and severity of aniseikonia. An objective test for aniseikonia does not currently exist. This study aims to assess different methods in quantifying structural asymmetries in the eye relative to subjectively measured aniseikonia, by severity, and which treatments most improve binocular summation, using electrodiagnostics and video oculography. Hypothesis: Small amounts of aniseikonia are objectively detectable, and correcting them can improve binocular summation as measured with visually-evoked potential (VEP) and visual performance using video oculography. Methods: 58 subjects (49 females, 9 males, mean age 27 ± 5.56 years) were studied structurally and functionally in this study. Seventeen participants had less than 0.50 D of spherical-equivalent myopia in both eyes, 11 had more than 1 D of anisometropia, with the remaining 30 having myopia in both eyes ≥ 0.50 D (Grand Seiko WAM- 5500). Structural asymmetry of the eyes was assessed based on axial length (Zeiss IOL Master 500), the geometric area and perimeter of the foveal avascular zone, and linear measurement of the distance between the macula and the temporal edge of the optic nerve using optical coherence tomography, with and without angiography (Optovue OCT-A and Cirrus OCT). Secondly, visual performance was compared in most of these participants, all with at least mild aniseikonia. Four optical treatments were tested, including iseikonic (size) lenses, prisms from associated phorometry, both size lens and prism together, and habitual correction only. These treatments were randomized with a Latin Square design. Performance measures with each treatment included monocular flicker electroretinography (ERG) magnitude and phase (n=51) and binocular summation with visually evoked potential (VEP) amplitude and latency (n=55), all measured objectively. Finally, a subset of the original participants (n=14) was evaluated with video oculography for visual performance, comparing habitual, iseikonic lenses, prism, and both. Results: Objective measurements included mean anisometropia (0.21 ± 0.89 D) and asymmetries in axial length (0.04 ± 0.59 mm), keratometry (0.20 ± 0.26 D), fovea-to-optic disc distance (106 ± 101 microns), foveal avascular zone (FAZ) area (0.37 ± 0.28 mm²), and FAZ perimeter (0.18 ± 0.16 mm). Subjectively, the absolute value of aniseikonia was 1.37 ± 0.63%. Small amounts of aniseikonia and structural asymmetry were measurably present in all participants studied. Results were compared with the non-parametric Kruskal-Wallis test. Aniseikonia correlated positively with axial length difference (Kruskal- Wallis H = 6.004, df = 2, p = 0.50) and prism correction of associated phoria (Kruskal-Wallis H = 7.57, df = 2, p = 0.023). The absence of anisiekonia was more often associated with similar axial length between the eyes (89%) than its presence was with difference in axial length (35%). Aniseikonia was not associated with anisometropia, keratometry differences, foveal avascular zone asymmetry, FAZ perimeter, or fovea-to-optic disc asymmetry in these mostly low-to-moderate aniseikonics. Functionally, aniseikonia was not associated with ERG magnitude or phase. Aniseikonia treatments (iseikonic lenses, prism, or both) did not significantly affect binocular summation as measured with visually evoked potential (VEP) amplitude or latency. In terms of visual performance, prism correction was significantly better for one of three saccadic activities as measured by video oculography, and slightly worse for the pursuit activity. Discussion and Conclusion: Aniseikonia can be present in the absence of anisometropia and differences in corneal power (keratometry). However, aniseikonia was associated with axial length differences between the eyes and associated phoria corrected by prism. Neither OCT measurement of the fovea to optic disc, FAZ area, nor FAZ perimeter asymmetry between the eyes was associated with aniseikonia in the mostly lowto- moderate aniseikonics studied. As measured objectively by visually evoked potential, binocular summation was not measurably improved by iseikonic lenses and/or prism in the population studied. A larger study including a larger number of high (≥3%) aniseikonics will be needed to determine any visual function changes that may occur when aniseikonia affecting sensory fusion is compensated for with iseikonic lenses and/or prismatic correction to strengthen motor fusion. Video oculography on a small (n=14) subset showed some promise for prism correction, modestly improving one of three saccadic activities while impairing smooth pursuits slightly.